Mass Cytometry and Single‐Cell RNA‐seq Profiling of the Heterogeneity in Human Peripheral Blood Mononuclear Cells Interacting with Silver Nanoparticles. Issue 21 (12th March 2020) - Ha, My Kieu; Kwon, Sook Jin; Choi, Jang‐Sik; Nguyen, Nguyen Thanh; Song, Jaewoo; Lee, Yangsoon; Kim, Young‐Eun; Shin, Incheol; Nam, Jin‐Wu; Yoon, Tae Hyun
Abstract: Understanding the interactions between nanoparticles (NPs) and human immune cells is necessary for justifying their utilization in consumer products and biomedical applications. However, conventional assays may be insufficient in describing the complexity and heterogeneity of cell–NP interactions. Herein, mass cytometry and single‐cell RNA‐sequencing (scRNA‐seq) are complementarily used to investigate the heterogeneous interactions between silver nanoparticles (AgNPs) and primary immune cells. Mass cytometry reveals the heterogeneous biodistribution of the positively charged polyethylenimine‐coated AgNPs in various cell types and finds that monocytes and B cells have higher association with the AgNPs than other populations. scRNA‐seq data of these two cell types demonstrate that each type has distinct responses to AgNP treatment: NRF2‐mediated oxidative stress is confined to B cells, whereas monocytes show Fcγ‐mediated phagocytosis. Besides the between‐population heterogeneity, analysis of single‐cell dose–response relationships further reveals within‐population diversity for the B cells and naïve CD4 + T cells. Distinct subsets having different levels of cellular responses with respect to their cellular AgNP doses are found. This study demonstrates that the complementary use of mass cytometry and scRNA‐seq is helpful for gaining in‐depth knowledge on the heterogeneous interactions between immune cells and NPs and can be incorporated into future toxicity assessments of nanomaterials. Abstract : The complementary use of mass cytometry and single‐cell RNA sequencing enables the analysis of the heterogeneous interaction between nanoparticles (NPs) and immune cells at a single‐cell level via the simultaneous identification of various immune cell types, quantification of cell‐associated NPs, as well as observation of the transcriptomic changes and signaling protein expressions of individual cells in each immune cell type.